Intrinsic factors affecting sheep meat quality: a review - de Lima Júnior, Dorgival M; de Carvalho, Francisco F R; da Silva, Felipe J S; Rangel, Adriano H do N; Novaes, Luciano P; Difante, Gelson dos S (Revista Colombiana de Ciencias Pecuarias, 2016)
The quality of meat is a multifactorial parameter dependent on the perspective and goals of the link in the production chain. Generally, a variety of factors directly or indirectly affect the quality characteristics of meat and, therefore, the value of meat products. Often, the literature divides the interfering factors into intrinsic and extrinsic. Intrinsic factors are related to animals; therefore, intrinsic factors are less variable. These factors include breed, sex, age, weight, genes, and type of muscle fiber. Some of these factors are not well studied, others have variable influence or are controversial and only a few are known and sometimes controlled. Thus, this study aimed to review some intrinsic factors that influence the quality of lamb meat.